Purification, characterization and antioxidant activity of selenium-containing polysaccharides from pennycress (Thlaspi arvense L.). (February 2022) - Xiang, Anni; Li, Wenting; Zhao, Yuning; Ju, Hongmei; Xu, Shuang; Zhao, Shiyu; Yue, Tianli; Yuan, Yahong
Abstract: Selenium polysaccharides have antioxidant, anti-tumor and other activities. Tea selenium polysaccharides and Lentinan selenium polysaccharides, etc. have been studied. Pennycress is a super-rich selenium plant and there are few studies about pennycress selenium-containing polysaccharides. In this study, the following researches were carried out on pennycress selenium polysaccharides: Selenium-containing polysaccharides were extracted from the leaves of pennycress ( Thlaspi arvense L.) using an efficient subcritical water extraction (SWE) process. After purification, two fractions (Se-PPS1 and Se-PPS3) were obtained and subjected to structural identification. The results showed that the molecular weights of Se-PPS1 and Se-PPS3 were 4.2 × 10 4  Da and 4.5 × 10 4  Da, respectively. Se-PPS1 is mainly comprised of glucose, galactose, and xylose. Se-PPS3 consists of glucuronic acid, rhamnose, galacturonic acid, glucose, galactose, xylose, and arabinose. Fourier transform infrared spectroscopy (FT-IR) analysis showed that the two fractions had absorption spectra typical of selenium esters and spectral characteristics of polysaccharides. The glycosidic linkages were determined by Gas chromatography-mass spectrometry (GC-MS) and Nuclear magnetic resonance (NMR). The two fractions have (1 → 6)-β-D- Gal p and T-α-D- Glc p configurations. Moreover, in vitro antioxidant activity assays showed that Se-PPS1 and Se-PPS3 exhibited effective radical-scavenging abilities, suggesting they have potential applications as natural antioxidants in food and medicine. Graphical abstract: Image 1 Highlights: Selenium-containing polysaccharides were extracted and purified from pennycress. Se-PPS1 and Se-PPS3 were characterized by FT-IR, GPC, HPLC, GC-MS, and NMR. Se-PPS3 fraction showed stronger scavenging activities than that of Se-PPS1. The fraction with uronic acid have stronger antioxidant capacity.